Entrepreneurial Abilities and Attitude of Business Students as Determinants of their Interest in Starting a Business - Suehara Vanity M. Barit (International Journal of Engineering and Management Research, 2023)
Studying personal characteristics plays a great influence in understanding entrepreneurial abilities and entrepreneurial attitude which are considered as varying factors in determining entrepreneurial interest as shown in several studies. Abilities are those which all individuals need for personal fulfillment and development and social inclusion and employment such as cognitive and non-cognitive abilities whilst entrepreneurial attitude is someone’s traits and behavior on the personal desirability in creating an enterprise. This study aims to assess if entrepreneurial abilities, both cognitive and non-cognitive skills, and attitude towards entrepreneurship significantly influence business students’ interest to start a business. This research utilized the descriptive research design. A researcher-made questionnaire was used as the main data gathering tool. The same instrument was pilot tested to check its internal consistency. Validity was determined through the assessment of the three experts consulted for the said purpose. A random sampling design was utilized in this study which led to involve 265 respondents from the four member schools of the private education network. Multiple linear regressions were used to determine the statistical significance of the influence that was tested. The results proved that both entrepreneurial ability and attitude towards entrepreneurship significantly influence student’s interest to start a business. Specifically, cognitive skills, and Self-efficacy, Social Orientation, and Motivating as non-cognitive skills are significant influencers to starting a business while Pro-activity is not found to have the same influence on the same. Finally, the study concludes that over-all attitudes towards entrepreneurship significantly influence a student’s decision to start a business. Calculated risk and need for achievement is found to have a significant influence on the intention to start a business while autonomy, creative tendency and drive and motivation were not found significant.